USES THE NUTRACEUTICALS OF TULASI (Ocimum sanctum L.) LEAF EXTRACT FOR ORODENTAL HEALTH: Penggunaan Nutraceutical Ekstrak Daun Tulasi (Ocimum Sanctum L.) Pada Kesehatan Gigi dan Mulut - I Gusti Ayu Ari Agung Ari Agung; Gusti Agung Ayu Hartini; Gusti Ayu Yohanna Lily; I Nyoman Panji Triadnya Palgunadi; Ilma Yudistian; Anak Agung Manik Swayoga (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
Introduction: Dental and oral health has an effect on general health. Orodental disease can be considered asIntroduction: Dental and oral health has an effect on general health. Orodental disease can be considered as a major public health problem. Tulasi (Ocimum sanctum L.) has been acknowledged for their beter remedial value and minimal side effects. Therefore, the purpose of writing this article is to review articles with the theme of uses nutraceutical Tulasi leaf extract for orodental health. Review: Tulasi contains good nutraceuticals, has great potential as an orodental health, such as antimicrobial, antiviral, antiinflammatory, antioxidant, immuno-modulatory activity, because of its role as superior with potential eugenol, linalool, ursolic acid, carracroland, terpenes, rosmarnic acid, and good nutrients such as stearic acid, palmiticacid, oleic acid, linoleic acid, beta carotene, vitamin C, calcium, potassium, zinc, manganese, and sodium. Conclusion: Nutraceuticals Tulasi leaf extract very well used for orodental health, as immunomodulatory, anticancer, antimicrobial, mouthwash, dentifrice, and gel.